2002
DOI: 10.1080/000163502753740188
|View full text |Cite
|
Sign up to set email alerts
|

Selection of criteria for assessment of occlusal acceptability

Abstract: There is no general agreement on criteria that could be applied to distinguish between orthodontically acceptable and non-acceptable occlusions after the completion of dental development. The aim of the present study was to analyse morphological and functional features that could be used as an index to define an acceptable occlusion in young adults. Three expert panels representing specialists in orthodontics and stomatognathic physiology participated in a modified Delphi method. Each panel responded to a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Delphi methods were deemed appropriate as healthcare professionals' communication of risk involves a blend of scientific evidence, social values and expert judgement. 17 The Delphi technique has been used to investigate risk disclosure for medical procedures, 18 develop clinical guidelines 19 and criteria to assess orthodontic outcomes 20 and assess the impact of reducing orthodontic treatment availability 21 . Other consensus development methods include the nominal group technique and consensus conferences.…”
Section: Discussionmentioning
confidence: 99%
“…Delphi methods were deemed appropriate as healthcare professionals' communication of risk involves a blend of scientific evidence, social values and expert judgement. 17 The Delphi technique has been used to investigate risk disclosure for medical procedures, 18 develop clinical guidelines 19 and criteria to assess orthodontic outcomes 20 and assess the impact of reducing orthodontic treatment availability 21 . Other consensus development methods include the nominal group technique and consensus conferences.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Group I consisted of subjects from three secondary schools and one vocational school in central Finland (n ϭ 116) aged between 16 and 25 years. Group II comprised 15-to 18-year-old subjects from the catchment area of one municipal health center in eastern Finland (n ϭ 192), and Group III comprised 16-year-old adolescents from a rural municipality in southwest Finland (n ϭ 126).…”
Section: Methodsmentioning
confidence: 99%
“…7,9,10 In a series of investigations, clinical criteria that could be used in the assessment of occlusal acceptability were analysed. [11][12][13][14] Consequently, a new index, the Occlusal Morphology and Function Index (OMFI), was developed, based on the assessment of six morphological and four functional criteria. 15,16 The OMFI is intended to be used as a tool eg, in studies monitoring the outcome of orthodontic care at population level.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with traditional screening methods, a study by Burden and Mitropolous (1992) showed that the use of the IOTN would increase the number of patients who would be selected for treatment. Swedström-Oristo et al (2002) found several dental criteria that differ between Finnish professionals and the DHC. The use of the DHC would therefore result in treating 50 per cent of the cases that they had rated as being acceptable (no treatment).…”
Section: Evaluation Of the Dhc Of The Iotnmentioning
confidence: 99%